The Image of the African Other in French Cinema During the Collapse of the Colonial Empire, 1945-1960 - Anton S. Gavrilov; Elena G. Zueva (Vestnik RUDN. International Relations, 2025)
As European society has become increasingly multicultural, interest in the problems of representation of ethnic and racial minorities in contemporary Western cinema has grown significantly. The processes taking place in Western cinema are a response to the political challenges posed by immigration, globalization and the problems of interethnic and international relations. According to some researchers, the roots of these problems should be sought in the colonial past. It is therefore particularly relevant today to look at the history of colonialism and its cultural aspects. Cinema as a historical source provides valuable insights into the manner in which the colonial era constructed cultural boundaries between the West and the East, as well as between the colonizer and the colonized Other. In particular, Third Republic films about colonies in Africa supported the colonial discourse of their time, reflecting the power of the French colonial empire, and portraying the colonizers as noble, brave, and selfless and the colonized “others” as exotic, savage, and rebellious. However, after the World War II, in the wake of decolonization, the relevance of previous approaches to representing the empire and its possessions was called into question. This article reveals the influence of the political decolonization process on the ideological content of French cinema about the Empire during specified period, the changing approaches to the visual representation of the colonized Other, and how these changes were perceived by the audience. According to the authors, such historical research can help to better understand the origins of modern phenomena in European cinema and Western culture in general. The work uses French films from 1945-1960 as historical sources. The authors examine cinema through the frame of postcolonial theory, as a tool for strengthening colonial power and forming ideas about the colonized Other. In analyzing the films, the authors use an approach that examines their genesis, content, cinematic imagery and public response. Based on the analysis, it is concluded that the need to soften the colonial discourse in the context of the Empire collapse led to the ideological content of the Fourth Republic’s cinema becoming more contradictory. It reflected, on the one hand, nostalgia for the past imperial greatness, and on the other, uncertainty, a desire to stay away from current problems, and even sympathy for the anticolonial movement. Stereotypical ideas about the colonized, although they did not completely disappear from the screens, still evolved along with how the empire itself transformed, giving rise to images of the Other that were atypical of the earlier period.